What Symmetry Can Do That Parallelism Can’t: Line Perception and Poetic Effects in the Song of Deborah (Judges 5:2–31) - Grosser, Emmylou J. (Vetus Testamentum, 2021)
The concept of parallelism has framed discussions of biblical poetry for more than two centuries, but there is still no consensus on what exactly parallelism is. This study contends that consensus does not exist because the side-by-side correspondence approach of parallelism is not suited to the part-whole free-rhythm nature of biblical poetic lines. Instead, perceptual symmetry better accounts for certain aspects of poetic lines that have been understood as parallelism. Unlike parallelism, symmetry is able to account for how lines emerge in aural, free-rhythm biblical poetry, as well as how the emergence of lines is intertwined with poetic effects, as demonstrated in the Song of Deborah (Judg 5:2–31). The cognitive poetics framework of this paper shifts scholarly focus from line patterns to the perception of these stimulus patterns, taking seriously the features of the text as well as the mental processing of the active listener.